Strategic planning: attracting investments in agro-industrial enterprises - D. S. Tusin (Вестник университета)
Since agriculture is  an important sector of   the Russian economy, the problem of   lack of   capital in   this industry is   still relevant. The article shows that the effective functioning of  agricultural enterprises in   modern conditions of a  dynamic and rapidly changing business environment in  the long term depends on  the development of   new and more advanced approaches to   investment planning. The problem of  the study is   related to   the absence or   imperfection of   strategic management of   investment policy at  many enterprises in   the agricultural sector, which leads to   their difficult financial situation, slows down their development and reduces competitiveness. The main purpose of   the presented research is  to form proposals for improving the strategic planning model by  developing and implementing investment strategies of   enterprises of   the agro-industrial complex (hereinafter referred to   as AIC). In   the course of   the study, a   review of   domestic and foreign literature has been conducted reflecting the issues of   the investment planning. Within the framework of   the modern approach to  the problem, the following research methods are used in   the article: literature analysis, classification, comparative analysis, description, observation, and statistical method. Special attention in  the methodology is   paid to   the digital transformation of   the investment activity of  the AIC in   Russia and the world. The author substantiates that the modern strategy of   attracting investments in   the AIC enterprises should radically differ from previous approaches and be  implemented with consideration to   the development of   the information technology market. It   is necessary that this approach facilitates the transition of   the Russian AIC to   the formats of   “Agriculture 4.0” and “Agriculture 5.0”.